Analysis of the internal control system for cash receipts and disbursements - Darul Fahmi; Novita Dwi Frasutiyo (Sean Institute, 2024)
This research describes implementing the internal control system for cash receipts and disbursements at the Purba Adhika Foundation. This research method uses primary data with observation, interview, and documentation data collection techniques; the analysis technique used in the research is qualitative description techniques. The Purba Adhika School Foundation is a special needs school that operates in education services. The results of this research found that the cash control system at the Purba Adhika Education Foundation still needs to be more effective and efficient. This can be seen by the absence of a financial function that regulates cash control, and financial reports are still centered on the Foundation. They have not been managed at each Purba Adhika School and still need to be fully managed. They are Using a computerized system.